Government Ecology and the Indigenous Religion of the Suku Anak Dalam: Intersubjective Relations in Forest Conservation in Jambi, Indonesia - Khairun Najib (Jurnal Manajemen Hutan Tropika, 2020)
Integrating customary-religious values of an indigenous tribe "Suku Anak Dalam” (SAD) and state zoning system in Bukit Duabelas National Park (TNBD), Jambi, Indonesia is a configuration of an intersubjective relationship between government ecology and the religion of indigenous SAD in forest conservation that has not been studied by previous researchers. Hence, this article discusses that intersubjective relationship practice in preserving, maintaining, and protecting sustainable forest by assimilating the SAD's customary-religious values and the state zoning system. Moreover, this article also complements the shortcomings of previous researchers who believe that SAD's cosmology is animistic and proves that the TNBD zoning system's implementation as a cause of the SAD conflict. After conducting the interviews and the observations supported by relevant literature sources, this article shows that the SAD believes that the cosmos is not only inhabited by humans, but there are nonhuman beings such as animals and Badewo who are perceived as a human in which they are believed as social actors in forest conservation. SAD and nonhuman beings live together and contribute to each other and have a mutual relationship to life sustainability in the forest or so-called indigenous religion. Besides, the article also found that the TNBD zoning system is not the primary cause of the SAD conflict, rather the dynamics process in integrating state zoning and indigenous custom-religious spaces between the TNBD offices and the SAD.